Spiritually Intelligent Leaders: The Way Forward - P. Kanniaseelan, K Sugitha (2009)
This study was undertaken with the aim to investigate the relationship between spiritual intelligence and individual performance in the organization. In this study, spiritual intelligence is defined as the ability to perform abstract reasoning by seeking answers from the deep person within, in attempt to solve problems.